Successful surgical closure and continence rate of obstetric fistula in Africa: systematic review and meta-analysis - Kumsa, Henok; Mislu, Esuyawkal; Arage, Mulugeta Wedaje; Abera, Atitegeb; Hailu, Tilahun; Tenaw, Lebeza Alemu (Frontiers in Global Women's Health, 2023)
Background A female genital fistula is an abnormal connection between a woman's reproductive tract and her urinary tract or rectum. While numerous studies have aimed to determine the success rate of obstetric fistula closure in different health settings, there remains a significant scarcity of data on closure success rates and incontinence rates for various types of fistulas at the regional and sub-regional levels. The success rate reflects the continent's healthcare setup in regard to the World Health Organization standards. Thus, this study aims to determine the success of surgical closure and the continence rate of obstetric fistula in Africa. Methods This systematic review and meta-analysis review includes studies conducted up to February 2023. Search engines like EMBBASE, Medline, Google, PubMed, Google Scholar, African Journals Online, and ScienceDirect databases were utilized to find articles. The Joanna Briggs Institute critical evaluation checklist was used to evaluate the quality of our review, which was conducted in accordance with PRISMA criteria. Heterogeneity was indicated by a p-value for I2 statistics of less than 0.05. Publication bias was assessed using the Egger regression asymmetry test. Data were entered into Microsoft Excel and analyzed using STATA 16. Result This review includes 85 studies. A total of 24 countries from East, West, Central, North, and Southern African sub-regions were included. The overall pooled estimated rate of successful obstetric fistula closure is 86.15 (95% CI: 83.88–88.42). Moreover, the pooled estimated rate of successfully closed vesico-vaginal fistulas but with ongoing or residual incontinence (wet) was revealed as 13.41% (95% CI: 11.15–15.68). The pooled estimated rate of successfully closed rectovaginal fistulas and combined VVF and RVF are 91.06% (95% CI: 86.08–96.03) and 62.21% (95% CI: 48.94–75.49), respectively. Conclusions The rate of successful obstetric fistula closure in Africa is 86.15, which is higher than the WHO target. However, the surgical closure rate of a combined VVF and RVF is 62.2%, which is significantly lower than the WHO target.